P-298 The live birth rate of the endometriosis patient is significantly increased by high luteal phase serum progesterone in HRT-FET cycles - A cohort study. (30th June 2022) - Alsbjerg, B; Kesmodel, U.S; Elbaek, H.O; Laursen, R; Povlsen, B.B; Humaidan, P
Abstract: Study question: What is the optimal serum progesterone (P4) cut-off level for endometriosis patients undergoing hormone replacement therapy frozen embryo transfer (HRT-FET) with intensive exogenous progesterone luteal phase support? Summary answer: Endometriosis patients with luteal serum P4 levels≥118nmol/l had significantly higher live birth rates (LBR) compared to patients with lower P4 levels. What is known already: A low luteal serum P4 level decreases the reproductive outcome of HRT-FET cycles in the "standard" patient, and an optimal cut-off level of 10ng/ml has been suggested. Interestingly, some studies reported a negative impact of too high serum P4 levels during HRT-FET. The pathology of endometriosis is dominated by an endometrial disruption of progesterone and oestrogen signalling pathways. This results in intra-endometrial oestrogen dominance, and leads to progesterone resistance which negatively impacts endometrial receptivity and function. Until now no study explored the optimal serum P4 level in the endometriosis patient undergoing HRT-FET. Study design, size, duration: A cohort study including 262 HRT-FET cycles in 179 patients, undergoing transfer of warmed blastocysts, deriving from freeze all cycles from January 2016 to august 2019. Participants/materials, setting, methods: Patients were diagnosed with endometriosis either by laparoscopy or by ultrasound in cases with visible endometriomas. Pre-treatment consisted of 42 days of oral contraceptive pill and 5 days' wash-out, followed by 6 mg oral oestrogen daily. Intensive exogenous progesterone supplementation, including vaginal progesterone gel 90mg/12h commenced when the endometrium was ≥7mm. From the 4th day of progesterone patients also received intramuscular progesterone 50mg. Blastocyst transfer was scheduled for the 6th day of progesterone. Main results and the role of chance: The mean P4 level was 103.1 ±44.4nmol/l and the overall positive HCG, live birth (LBR) and total pregnancy loss rates (TPLR) were 60%, 39% and 34%, respectively. The optimal serum P4 cut-off level was 118nmol/l defined as the maximum of the Youden index. No significant differences were seen between patients above or below 118nmol/l as regards age, BMI, fertilisation method or blastocyst score. In a total of 33% of cycles (86/262) the P4 level was ≥118nmol/l, and the unadjusted LBR was significantly higher in the high P4 group 51% (44/86) versus 34% (59/176) (p = 0.006) in the low P4 group. Furthermore, a non-significant difference in TPLR was found: 41% vs 25 % in favour of high P4 (p = 0.066). A logistic regression analysis showed that patients with P4 levels ≥118nmol/l were more likely to achieve a live birth compared to patients with P4 levels <118nmol/l; (odds ratio 2.1 [95% confidence interval 1.2 - 3.7] after adjusting for age, BMI, blastocyst score, blastocyst age (day 5 or day 6) and number of blastocysts transferred. Limitations, reasons for caution: Cohort study with data prospectively registered and retrospectively analyzed. The estimated serum cut-off for P4 of 118nmol/l is valid for vaginal progesterone gel 90mg/12h and intramuscular progesterone 50mg from the 4th progesterone day; whether the cut-off is applicable for other progesterone regimens needs to be explored. Wider implications of the findings: The optimal luteal P4 level of the endometriosis patient undergoing HRT-FET is significantly higher than that estimated for the "standard" patient due to endometrial progesterone resistance. Luteal phase P4 monitoring is mandatory to obtain the highest LBR in the endometriosis patient undergoing HRT-FET. Trial registration number: 1-10-72-4-17